2016
DOI: 10.5498/wjp.v6.i2.248
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis of relationship among personality, perceived stress, coping, social support, and psychological outcomes

Abstract: Personal resources play an important role in reduction and prevention of anxiety and depression. In order to improve the psychological health, it is necessary to train and reinforce the adaptive coping strategies and social support, and thus, to moderate negative personality traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 49 publications
4
32
0
11
Order By: Relevance
“…These findings coincide to a large degree with the results obtained in studies with other populations (Carver and Connor-Smith, 2010;Grant and Langan-Fox, 2006;McCrae and Costa, 1986;Roohafza et al, 2016), pointing to extraversion, agreeableness, conscientiousness, and openness as predictor traits of coping more dedicated to problem-solving; neuroticism as a predictor of more passive and avoidance coping, related to emotion-focused strategies; and conscientiousness and agreeableness as negative predictors of emotion-focused strategies (Carver and Connor-Smith, 2010;McCrae and Costa, 1986). Although these complex associations can be nuanced by moderator, contextual, and appraisal variables, Carver and Connor-Smith (2010) mention that these associations provide an elaborated view of the way traits influence behavior, and with regard to coping, they provide a clearer view of who can be expected to engage in what type of coping.…”
Section: Discussionsupporting
confidence: 90%
“…These findings coincide to a large degree with the results obtained in studies with other populations (Carver and Connor-Smith, 2010;Grant and Langan-Fox, 2006;McCrae and Costa, 1986;Roohafza et al, 2016), pointing to extraversion, agreeableness, conscientiousness, and openness as predictor traits of coping more dedicated to problem-solving; neuroticism as a predictor of more passive and avoidance coping, related to emotion-focused strategies; and conscientiousness and agreeableness as negative predictors of emotion-focused strategies (Carver and Connor-Smith, 2010;McCrae and Costa, 1986). Although these complex associations can be nuanced by moderator, contextual, and appraisal variables, Carver and Connor-Smith (2010) mention that these associations provide an elaborated view of the way traits influence behavior, and with regard to coping, they provide a clearer view of who can be expected to engage in what type of coping.…”
Section: Discussionsupporting
confidence: 90%
“…A total of 30 studies were found that adhered to the inclusion criteria set for the systematic review. Of these, 16 focused on social support and psychological outcomes (Abu-Kaf et al, 2018;Adamczyk, 2015;Bíró, Veres-Balajti, & Kósa, 2016;Ceglarek & Ward, 2016;Frison & Eggermont, 2015;Kim, Kim, & Lee, 2016;Llamas, Morgan Consoli, Hendricks, & Nguyen, 2018;Marhamah & Hamzah, 2016;Ng, Wang, & Chan, 2017;Roohafza et al, 2016;Tang & Dai, 2018;Vungkhanching, Tonsing, & Tonsing, 2016;Wang, Sun, & Wang, 2016;Wongtongkam, 2019;Yıldırım, Karaca, Cangur, Acıkgoz, & Akkus, 2017;You, Lim, & Kim, 2017); 3 focused on social support and academic achievement (Bai et al, al., 2018; Rodríguez et al, 2017); 4 focused on social support and technology use (Deechuay, Koul, Maneewan & Lerdpornkulrat, 2016;Gökçearslan, Uluyol & Şahin, 2018;Shah, Siddiqui & Ansari, 2016;; 4 focused on sources of social support (Bhochhibhoya et al, 2017;Chuah & Singh, 2016;Lee & Goldstein, 2016;Rios & Eaton, 2016); and 3 focused exclusively on gender differences in social support (Lin, 2016;Zamani-Alavijeh, Raeesi Dehkordi, & Shahry, 2017;Zhang, Zhapng, Zhang, Zhang, & Feng, 2018). All studies except one were quantitative.…”
Section: Research Resultsmentioning
confidence: 99%
“…In terms of sample, the lowest sample size of male participants in any included study was 9, while the highest sample size of male participants in any included study was 2106. With regards to the instruments used to measure social support, there was wide variation, although Multidimensional Scale of Perceived Social Support emerged as the most used instrument to measure social support among undergraduates (Adamczyk, 2015;Frison & Eggermont, 2015;Lee & Goldstein, 2016;Li et al, 2018;Roohafza et al, 2016;Wongtongkam, 2019;Yıldırım et al, 2017;. Other instruments used to measure social support included Perceived Social Support Scale (Gökçearslan et al, 2018;Wang et al, 2016), Social Support Rating Scale (Shah et al, 2016;Tang & Dai, 2018), Social and Emotional Health Survey (You et al, 2017;, MOS Social Support Survey (Ceglarek & Ward, 2016), Multi-Dimensional Support Scale (Ng et al, 2017), Perceived Acceptance Scale (Rodríguez et al, 2017), and Social Support Questionnaire (Bai et al, 2018).…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, measures of perceived stress by definition emphasize the subjective appraisal of objective circumstances (Cohen, Kessler, & Gordon, ). As such, these measures will be influenced by a range of factors related to the individual, for example psychological symptoms, concurrent mood states, and personality dispositions (Ebstrup, Eplov, Pisinger, & Jørgensen, ; Roohafza et al, ). In fact, neuroticism can be characterized as “an enduring disposition to experience psychological distress” (Costa & McCrae, , p. 23), and measures of perceived stress and neuroticism tend to have items that overlap or resemble each other closely, such as “I often feel tense and jittery” (Costa & McCrae, ).…”
Section: Introductionmentioning
confidence: 99%